2019
DOI: 10.1007/978-3-030-31517-7_8
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Flakiness and Fragility of Randoop Regression Test Suites

Abstract: Randoop is a well-known tool that proposes a feedbackdirected algorithm for automatic and random generation of unit tests for a given Java class. It automatically generates two test suites for the class under test: 1) an error-revealing test suite, and 2) a regression test suite. Despite successful experiences with applying Randoop on real world projects like Java Development Kit (JDK) which have led to creation of error-revealing tests and identification of real bugs, it has not been investigated in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Microsoft deemed flaky tests as one of the most important reasons that impede software deployment period [4]. Beyond these industrial cases, flaky tests were also found to appear among automatically-generated tests by famous tools such as Randoop [5], Evosuite [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Microsoft deemed flaky tests as one of the most important reasons that impede software deployment period [4]. Beyond these industrial cases, flaky tests were also found to appear among automatically-generated tests by famous tools such as Randoop [5], Evosuite [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, a study on 211 projects in Apache Software Foundation showed that 21% of false alarms (false fail results) are created by flaky tests 7 . Another research work published in 2019 reports 5% flaky tests in Randoop (Obtained from five open‐source Java projects with a total of 78 versions) 8 . Moreover, Microsoft confirmed flaky tests to be the second most important reason (out of 10 reasons) adversely affecting software deployment time 9 .…”
Section: Introductionmentioning
confidence: 99%